Chemical investigation of Fe3+/Nb5+-doped barium titanate ceramics - L. Srisombat (2018)
Renewed interest in the perovskite ferroelectric barium titanate (BaTiO 3 ) has been driven by the introduction of large recoverable electrostrain in doped BaTiO 3 -based materials. Our previous work demonstrated that the potential for high-performance in Pb-free ferroelectrics based on BaTiO 3 was confirmed in Fe 3+ /Nb 5+ -doped BaTiO 3 systems. It is well documented that the electronic behavior of BaTiO 3 is intimately related to the chemical state of the constituents. However, information regarding the chemical states of the ions of the Fe 3+ /Nb 5+ -doped BaTiO 3 ceramics is currently unavailable. Consequently, this study describes the chemical state of sintered hybrid Fe 3+ /Nb 5+ -doped BaTiO 3 ceramics, compared with undoped BaTiO 3 ceramics derived from the same processing. Analysis by X-ray photoelectron spectroscopy (XPS) showed that the binding energy of Ti indicates the presence of more than one component of Ti within the doped BaTiO 3 ceramics, but only one component of Ti within the undoped BaTiO 3 ceramics. Unlike Ti, the XPS spectra indicates that more than one type of barium and oxygen species exist in both undoped and doped BaTiO 3 ceramics. © 2012 Elsevier Ltd and Techna Group S.r.l.